Islamic Traditional Education: A Comparative Perspectives from Nigeria's Makarantar Allo to Indonesia's Pesantren - Nasir, Muhammad Muhammad (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This study examines the historical evolution of Makarantar Allo in northern Nigeria and Pesantren in Indonesia, comparing their structures and operations across colonial, post-colonial, and contemporary periods. The focus on these institutions is driven by their similarities and the potential application of Indonesia's Islamic educational standards to enhance Nigeria's existing system. Incorporating a mixed-methods approach, this study collected primary data through interviews, focus group discussions and participant observations in Indonesia while engaging in the Makarantar Allo setting in Nigeria. Secondary data, consisting of historical facts, were gathered through document analysis. The analysis involved qualitative methods, verified through triangulation and cross-referencing with historical records. The research provides insights into the efficacy of Islamic education in Indonesia and Nigeria, highlighting differences and similarities. Pesantren in Indonesia operates centrally regulated, while Nigeria's Makarantar Allo is decentralized and unfunded. The comparative analysis suggests potential lessons for Nigeria's policymakers to improve the structure of Makarantar Allo based on the centralized Indonesian model, offering valuable standards for similar institutions with similar objectives in other Muslim countries. This research addresses a gap in the existing literature by comparing two traditional institutes, Makarantar Allo and Pesantren. The study explores their evolution, analysing their histories, curricula, teaching methods, structures, and challenges. This comparative pattern contributes to the novelty of the research, providing valuable insights into the unique characteristics and shared aspects of these traditional Islamic education systems.